FACTORS THAT INFLUENCING URBAN SPRAWL IN NORTH BANDUNG AREA - Fitriansyah, Luthfi
The development of Metropolitan Bandung Raya has encouraged the increasing needs of the community against the primary facility one of which is settlement. However to meet a demand there are constraints of availability and price of land in the city of Bandung, so people tend to find land settlements around the city of Bandung one of them in West Bandung regency and Bandung regency included into the area of North Bandung. This encourages the development of land that is expanding and sprawl, so basically threatening the sustainability of North Bandung Region. This study aims to identify the factors that influence urban crises in North Bandung area. So in the research conducted identification of land use changes in North Bandung area, then see the extent of urban sprawl symptoms that occur in North Bandung area so it can be known spatial patterns and factors that affect urban sprawl in the area of North Bandung. From the analysis result, it is known that sprawl index value in North Bandung area does not reach 1 (one) so that the sprawl index is compared with Metropolitan Bandung Raya, the result is sprawl index value from North Bandung area bigger than Metropolitan Bandung Raya. Thus shows that the existence of urban sprawl symptoms in North Bandung region based on the results of these comparisons. Further observed the spatial pattern of urban sprawl that occurred in North Bandung area is known that villages with high index value sprawl also have KWTa value with high and very high category deviation. There are at least 5 (five) villages that have KWTa values with high and very high deviations. From 5 (five) villages there are some similarities that is 10Km-15Km distance from the city of Bandung and in the availability of road infrastructure included in the category of medium to high. Based on the analysis that has been done is known that the main factors that affect the urban sprawl in the KBU is a factor of utility in this case is the availability of road infrastructure that affects the accessibility and distance factors village against the city of Bandung. But besides that there is also a supporting factor that is the physical characteristics of the availability of land suitable for land settled and regulatory factors.